Management Challenges of Marine Ornamental Fish and Their Utilization as The Sustainable Potential Marine Resources - Sapto Andriyono; Gde Raka Angg Kartika; Ahmad Fahrul Syarif; Md. Jobaidul Alam (Journal of Aquaculture Science, 2024)
Coral ornamental fish become potential fishery commodities, providing opportunities and challenges in managing fishery resources in Indonesia. This activity has long been done and has become one cause of damage to coral reefs in Indonesia. Changes in paradigm and technology currently applied in Indonesia are expected to provide a gradual regulatory and coral reef ecosystem improvement. The commercial trade of ornamental fish requires attention and rigorous regulation. The marine ornamental fish trade activity is expected to improve and drive the coastal communities' economy. The significant increase in exploitation is expected to be controlled with the right regulations. This regulation must refer to the concept of sustainable development established through the Sustainable Development Goals (SDGs), especially SDGs number 14 concerning life underwater. The existence of reef fish is enough to provide economic movement, which continues to heat up, especially after the pandemic and the reopening of flights and export activities abroad. However, multi-stakeholders should ratify the concept of sustainability and environment-friendliness. Support from the government, academia, industry, and community groups must be aligned and in tune to achieve sustainable development goals. Providing accurate information related to the biological characteristics of reef fish is an essential contribution for researchers that can be used directly by the community. Thus, the exploitation of reef fish can align with efforts to conserve coral reef ecosystems closely related to global warming and climate change.